2017
DOI: 10.1111/jfb.13250
|View full text |Cite
|
Sign up to set email alerts
|

Validation of daily increment deposition and early growth of mud carp Cirrhinus molitorella

Abstract: In this study, laboratory reared Cirrhinus molitorella from hatching through to the juvenile stage were used to validate daily increment deposition. Lapilli were suitable for ageing C. molitorella. The slope of the linear relationships between increment counts and age was not significantly different from 1 (n = 258, P > 0·05), indicating that growth increments are deposited daily. The first increment following the first-feeding check formed 3 days post hatch (dph). One hundred and twenty-three juveniles, rangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Studies have sometimes neglected the timing of the first increment formation (Pitcher, ; Fowler, ) or assumed that it occurred during a particular event in the fish life history (Campana & Neilson, ; Vilizzi, ). Indeed, the first increment may form before hatching in the case of Oncorhynchus nerka (Walbaum 1792) and Cyprinus carpio L. 1758 (Marshall & Parker, ; Smith & Walker, ) or a few days after the hatching time [ e.g ., Engraulis mordax Girard 1854, Solea solea (L. 1758), Cirrhinus molitorella (Valenciennes 1844)], which can correspond to yolk absorption or to the mouth opening and the first feeding (Brothers et al ., ; Jenkins, ; Lagardère & Troadec, ; Huang et al ., ). Assessing the time of first increment formation is therefore essential, as a failure to do so would lead to a consistent bias in age estimation (Campana, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have sometimes neglected the timing of the first increment formation (Pitcher, ; Fowler, ) or assumed that it occurred during a particular event in the fish life history (Campana & Neilson, ; Vilizzi, ). Indeed, the first increment may form before hatching in the case of Oncorhynchus nerka (Walbaum 1792) and Cyprinus carpio L. 1758 (Marshall & Parker, ; Smith & Walker, ) or a few days after the hatching time [ e.g ., Engraulis mordax Girard 1854, Solea solea (L. 1758), Cirrhinus molitorella (Valenciennes 1844)], which can correspond to yolk absorption or to the mouth opening and the first feeding (Brothers et al ., ; Jenkins, ; Lagardère & Troadec, ; Huang et al ., ). Assessing the time of first increment formation is therefore essential, as a failure to do so would lead to a consistent bias in age estimation (Campana, ).…”
Section: Discussionmentioning
confidence: 99%
“…The validation process is therefore essential to estimate fish age precisely. Previous validation studies on a dozen other cyprinids have shown the deposition of both daily and annual increments in otoliths (Victor & Brothers, 1982;Durham & Wilde, 2008;Ding et al, 2015;Yan et al, 2017;Huang et al, 2017), but a specific validation for each species is still required to avoid misinterpretation (Van Oosten, 1941;Beamish & McFarlane, 1983).…”
Section: Validation Of Daily Incrementmentioning
confidence: 99%
“…C. molitorella are currently often cultured in ponds with little water movement and are generally provided with excess feed containing heavy metals with the aim of achieving high yields and profits. Commercial fish feed with an appropriate heavy metal content can promote fish growth under scientific feeding methods, proper water flow, and a certain amount of submerged vegetation which can absorb heavy metals (Yang et al, 2018;Huang et al, 2017). Overfeeding -when fish are provided with excess commercial feed containing heavy metals-causes environmental pollution and the accumulation of metals in fish tissues (Xing, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Otoliths have consisted calcium carbonate located at the inner ear of bony fishes and also they are considered as a true biological and environmental archive of fish life history. Therefore, otoliths are used in different types of studies such as age determination, species identification and discrimination, larval fish ecology, migration of fishes etc (Brazner et al, 2004;Campana, 2005;Popper et al, 2005;Secor, 2010;Huang et al, 2017;Lin et al, 2017;Prichard et al, 2018). This calcified structure shows phenotypic plasticity as inter-and/or intra-specific and inter-and/or intra-populations variations (Annabi et al, 2013;Mejri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%